ANALISIS HUBUNGAN PROFESIONAL PERAWAT PELAKSANA DALAM MENYELESAIKAN ASUHAN KEPERAWATAN KEGAWATDARURATAN DI RUANG RAWAT INAP RST dr REKSODIWIRYO PADANG - astri doris (Akper Kesdam I/Bukit Barisan Padang, 2022)
Professional interaction is the interaction that occurs between nurses and patients, nurses and nurses, and nurses and other health professionals when providing services to patients. This relationship includes professional communication, partnership documentation systems, shift shifts, initial and final conferences, teamwork and leadership skills. The purpose of this study was to describe the professional relationship of the implementing nurse in the inpatient ward. This type of research is quantitative with a descriptive study and a cross-sectional approach, a proportional random sampling technique with a large sample of 88 people who are inpatient nurses. The results showed that the professional relationship in the inpatient room (56.8%) had a good relationship between nurses and the majority (43.2%) had a bad relationship. Based on the results of the study, it is recommended that nurses in inpatient rooms be able to carry out professional relationships between nurses and other health workers and patients, especially in terms of professional communication, so that the services provided can be provided optimally.